Pengaruh Profitabilitas, Leverage, Good Corporate Governance dan Ukuran Perusahaan Terhadap Agresivitas Pajak (Studi Kasus Pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Silvia; Mahanani, Setyo; Komilova, Irodakhon (Universitas Negeri Semarang, 2024)
This research is a quantitative study that aims to analyze the effect of profitability, leverage, independent commissioners, audit committees and company size on tax aggressiveness in Mining Companies listed on the Indonesia Stock Exchange in 2018-2021. The sampling technique used in this study was non-probability sampling using a purposive sampling approach and a sample of 26 companies was obtained. The data used is secondary data in the form of financial reports and annual reports obtained through the site www.idx.co.id and related company websites. The results of this study indicate that profitability, leverage, audit committee and company size have no effect on tax aggressiveness. Meanwhile, independent commissioners have a positive and significant effect on tax aggressiveness.